TOKOH-TOKOH KRITIKUS SASTRA ARAB ERA SADR ISLAM (AWAL ISLAM) - Rizki Hidayatullah, Muhammad (SHAWTUL ARAB, 2023)
This study aims to describe the figures of Arabic literary critics in the Islamic sadr era. The method in this study is qualitative method with descriptive analysis and literature study or library research. Researchers searched and collected data related to the content of the study, namely about the figures of Arabic literary criticism in the early days of Islam. These figures of early Islamic Arabic literary criticism as material objects in this study. Then the author uses a free translation system, which takes data in Arabic and then translates it into Indonesian. The results of this study show that these critical figures were very influential in the early days of Islam. Like Hasan bin Thabit a poet and critukus figure who was very close to the Prophet until he was called sya'ru Rasulillah (poet of the Prophet of Allah). Ka'ab bin Malik as a poet figure who was very brave and in assisting the Messenger of Allah in war and his sha'ir verses that tell a lot about the atmosphere during the war. Then Abdullah bin Rawahah as a figure or poet trusted by the Prophet both from his poetry and when on the battlefield. And that belief was not wasted by Rawahah until he risked his life to defend the religion of Iahmadslam